2020
DOI: 10.1039/d0ta00690d
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of the thermoelectric performance of LaZnOPn (Pn = P, As)

Abstract: State-of-the-art density functional theory is used to demonstrate that LaZnOP and LaZnOAs have great potential as earth-abundant p-type thermoelectric materials for high-temperature applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…25 However, systems which contain O 2 -and and another anion, for example BiCuOSe, show good p-type dopability and have emerged as promising p-type thermoelectrics. [26][27][28] In a recent computational study, 29 X 4 Y 2 Z mixed-anion compounds (X = Mg, Ca, Sr, Ba; Y = P, As, Sb, Bi; and Z = S, Se, Te) have been predicted to possess band gaps in the range suitable for many renewable-energy applications including as thermoelectrics. The study also revealed high band degeneracies, indicative of high power factors, and the complex crystal structures were found to yield low lattice thermal conductivities, with the room temperature κ l of Ba 4 Sb 2 Se being comparable to the flagship thermoelectric SnSe.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, systems which contain O 2 -and and another anion, for example BiCuOSe, show good p-type dopability and have emerged as promising p-type thermoelectrics. [26][27][28] In a recent computational study, 29 X 4 Y 2 Z mixed-anion compounds (X = Mg, Ca, Sr, Ba; Y = P, As, Sb, Bi; and Z = S, Se, Te) have been predicted to possess band gaps in the range suitable for many renewable-energy applications including as thermoelectrics. The study also revealed high band degeneracies, indicative of high power factors, and the complex crystal structures were found to yield low lattice thermal conductivities, with the room temperature κ l of Ba 4 Sb 2 Se being comparable to the flagship thermoelectric SnSe.…”
Section: Introductionmentioning
confidence: 99%
“…This is compared to typical ntype materials, which tend to have a much larger electron affinity which drives occupation of the conduction band by electrons. 77 The ionisation potential of CaCuP is relatively low, indicating that hole formation is easily achievable -indeed, films of CaCuP dis-play hole (Hall) concentrations on the order of 1 × 10 20 cm −3 . In fact, the ionisation potential is lower than that of CuI, which suggests that an overall higher concentration of holes could be achieved with an optimised deposition process.…”
Section: Band Alignmentmentioning
confidence: 99%
“…In principle, using the BoltzTraP, the electrical conductivity can be estimated only if the electronic relaxation time (τ) is given. Here, τ is determined by the comparison between calculated σ/τ value and reported σ (see comparison details and Supplementary Figure 6B in the Supplementary Materials) [25] , which has been widely employed in the evaluation of relaxation time for many materials [45][46][47] . The resulting τ values of stacking GST-I at different temperatures are shown in Supplementary Figure 6C, in which τ decreases with temperature (e.g., 20.1 fs at 310 K, 11.8 fs at 520 K, and 7.0 fs at 710 K).…”
Section: Electrical Transport Propertiesmentioning
confidence: 99%